2009
DOI: 10.1007/s00774-009-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower bone mineral density in children with type 1 diabetes is associated with poor glycemic control and higher serum ICAM-1 and urinary isoprostane levels

Abstract: The purpose of the study was to investigate bone mineral density (BMD) in children with type 1 diabetes (DM1) and to establish the relationships between BMD, physical activity, glycemic control, and markers of systemic oxidative stress and inflammation. We studied 30 children with DM1, aged 4.7-18.6 years, and 30 healthy subjects, matched by sex, age, and body mass index (BMI). Mean duration of DM1 was 5.4 +/- 3.4 years and mean glycosylated hemoglobin (HbA(1c)) level over 12 months was 9.8 +/- 1.5%. Lumbar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 32 publications
4
55
0
2
Order By: Relevance
“…A negative influence of type 1 diabetes on bone has been observed in a number of case-control studies conducted in adults [2,22] as well as in children and adolescents [1,4,6,[23][24][25], where peripheral and axial DXA and QCT were employed. It has been suggested that observed differences in adults may result from mineralisation disorders, which operate during rapid skeletal development in puberty.…”
Section: Discussionmentioning
confidence: 99%
“…A negative influence of type 1 diabetes on bone has been observed in a number of case-control studies conducted in adults [2,22] as well as in children and adolescents [1,4,6,[23][24][25], where peripheral and axial DXA and QCT were employed. It has been suggested that observed differences in adults may result from mineralisation disorders, which operate during rapid skeletal development in puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, however, documented the presence of osteopenia at diagnosis of diabetes (35). As depicted in Table 1, BMD correlated poorly with glycaemic control in most (29,33,34,35,36,37), but not all (28,31,32), studies. However many studies reported an association between the presence of microvascular complications of diabetes and the presence and/or progression of a decreased BMD (27,28,38,40,42,50).…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
“…Although the decreased BMD reported in subjects with T1DM (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,50,58) may largely explain the higher fracture risk observed in these patients (17,18,19,20,21,22,26), alterations in bone quality, as described below, may also contribute and actually confer its specific nature to diabetic bone disease.…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 DM, also known as insulindependent DM, results from insulin insufficiency which leads to hyper glycemia in the young [20] . Besides the usual neurovascular complications, both male and female patients with type 1 DM manifest low bone mass at the hip, femoral neck and spine (Table 1), which may eventually lead to an increased incidence of bone fractures [2225,28,29] . In contrast, data on skeletal abnormalities in type 2 DM, or non insulin-dependent DM, appear conflicting, and the exact explanation of this is still unknown [26,27,30] .…”
Section: Dm-induced Osteoporosismentioning
confidence: 99%